Genomic hallmarks of endocrine therapy resistance in ER/PR+HER2- breast tumours - Arnab Ghosh; Rohan Chaubal; Chitrarpita Das; Pallavi Parab; Subrata Das; Arindam Maitra; Partha P. Majumder; Sudeep Gupta; Nidhan K. Biswas (Communications Biology)
Abstract ER/PR+HER2- breast tumours are the most predominant subtype of breast cancer worldwide, including India. Unlike TNBCs, these tumours can be treated with anti-estrogens or aromatase inhibitors. Despite the success of endocrine therapy, a fraction of patients with ER/PR+ breast tumours do not respond to hormone-receptor-specific treatment and encounter disease recurrence contributing to their poor survival. The genomic underpinnings of therapy resistance in ER/PR+HER2- breast tumours are incompletely understood. We have performed whole genome sequencing (WGS) from tumour and normal tissue samples from endocrine-therapy resistant ER/PR+HER2- breast cancer patients who have relapsed on endocrine therapy and have conducted a comparative analysis of WGS data generated from tissues of endocrine therapy sensitive patients who remained free of disease during a minimum 5-year follow-up. Our analysis shows (a) a three-gene (PIK3CA-ESR1-TP53) resistance signature, and (b) impaired DNA double-strand break repair and homologous recombination pathways, were significantly associated with endocrine-therapy resistance and disease recurrence in ER/PR+HER2- tumours. Genome instability, contributing to high burden of copy-number, structural alterations and telomere-shortening identified as major markers of endocrine treatment resistance. Early prediction of endocrine-therapy resistance from the genomic landscape of breast tumours will aid therapeutics. Our finding also opens up the possibility of repurposing PARP inhibitors in treating endocrine therapy-resistant breast cancer patients.